STATUS PERWALIAN ANAK ZINA DAN PERAN PENGHULU DI KUA DALAM PERNIKAHAN MENURUT HUKUM ISLAM DAN UNDANG-UNDANG - Nur Roihanah, Ulfiyani; Khoirinnisah, Ira (Muadalah : Jurnal Hukum, 2023)
This research aims to understand the implementation of marital guardianship for illegitimate children and explain the Islamic Law view of this practice at the Office of Religious Affairs. In exploring the details of the implementation of marriage guardianship, the method used is qualitative descriptive with data obtained through the literature. The results of the research show that the marital guardianship of illegitimate children at the KUA is recognized as valid according to Islamic law, with the main basis being the use of Islamic law such as the Koran and Hadith, especially in involving guardian judges. The KUA uses guardian judges with caution to determine a law, then for preventive efforts, namely emphasizing the importance of the sacredness of marriage physically and mentally, so that it is not influenced by relationships that are not permitted in religion. This research aims to understand the implementation of marital guardianship for illegitimate children and explain the Islamic Law view of this practice at the Office of Religious Affairs. In exploring the details of the implementation of marriage guardianship, the method used is qualitative descriptive with data obtained through the literature. The results of the research show that the marital guardianship of illegitimate children at the KUA is recognized as valid according to Islamic law, with the main basis being the use of Islamic law such as the Koran and Hadith, especially in involving guardian judges. The KUA uses guardian judges with caution to determine a law, then for preventive efforts, namely emphasizing the importance of the sacredness of marriage physically and mentally, so that it is not influenced by relationships that are not permitted in religion.